Seismic Safety Review of Gravity Dam Based on Finite Element Method - Guanchao Xu; Bowen Guo; Zhuolun Meng; Jiwei Zhao (Geofluids)
With the change of the seismic parameter zoning map of China (GB 18306-2015), the seismic grade of reservoir dams in some areas had changed. At the same time, the standard for seismic design of hydraulic structures (GB 51247-2018) also put forward new requirements for the seismic calculation of reservoir dams. In order to ensure the safe operation of reservoir dams, it is necessary to review the seismic safety based on the finite element numerical simulation technology. Taking the retaining dam section of a gravity dam as an example, a finite element model of the retaining dam section was established, the corresponding calculation and analysis of ground motion were carried out using the mode decomposition response spectrum method, and the seismic safety evaluation of the retaining dam section was carried out according to the calculation results. The results show the following: (1) after considering the effect of hydrodynamic pressure, the natural frequency of the dam body has been significantly reduced, and the first-order natural frequency has been reduced by about 10%; (2) in addition to the local tensile stress at the dam heel, the rest of the vertical stress on the foundation surface of the retaining dam section is compressive stress, and the length of the tensile stress is less than the distance from the dam heel to the curtain center line, which met the requirements; (3) the antisliding stability safety factor of the retaining dam section is greater than the design value in the specification and meets the safety requirements; and (4) the seismic safety of the retaining dam section meets the standard requirements, and the seismic grade is evaluated as grade A.